The impact of cardiovascular drug innovation on the longevity of elderly residents of Switzerland, 2003-2012 - Frank R Lichtenberg (University of Oslo, 2015)
Previous investigators have argued that one of the two most important contributors to improved human survival is the treatment of cardiovascular disease. Among Swiss inhabitants age 65 and over, 90% of the 1994-2010 decline in the overall death rate was due to the decline in the rate of deaths from diseases of the circulatory system. Little if any of the decline in cardiovascular mortality is likely to have been due to changes in behavioral risk factors, especially tobacco use and obesity. This study examines the impact of cardiovascular drug innovation on the longevity of elderly residents of Switzerland using cross-sectional patient-level data on about 22 thousand patients insured by a major health insurer (CSS) during the period 2003-2011. We investigate the effect of the vintage (world launch year) of the cardiovascular drugs used by an individual in 2003 on his or her longevity (time till death), controlling for several demographic characteristics and indicators of health status. We are able to track a patient's vital status until 12/31/2011: 8 years after the end of the period in which cardiovascular drug use (and other variables) are measured. Our estimates indicate that people who used newer cardiovascular drugs in 2003 had longer time till death than people who used older cardiovascular drugs, controlling for the number of 2003 prescriptions and their distribution by main anatomical group, the number of 2003 doctor visits and their distribution by specialty, whether the person was hospitalized in 2003, sex, and age. Our most conservative estimates imply that cardiovascular drug innovation accounted for almost a quarter of the increase in longevity among elderly residents of Switzerland during 2003-2012, and that it increased their longevity by almost 3 months. Other estimates are about twice as large. All of the estimates are consistent with the hypothesis that newer classes of drugs tend to be therapeutically superior to older classes of drugs, and that newer drugs tend to be superior to older drugs within the same class. Even our more conservative estimates indicate that the use of new cardiovascular drugs by elderly residents of Switzerland has been highly cost effective. Our conservative estimate of the cost per life-year gained from cardiovascular drug innovation is below $10,000, and some economists have argued that the value of a statistical life-year is as high as $300,000.